Cultural and Philosophical Meanings of Sodoran Dance - Trisakti Trisakti; Anik Juwariyah; Fithriyah Inda Nur Abida (RIRAI Publisher, 2022)
The purpose of this research is to analyze the cultural values contained in the sodoran dance. Sodoran dance is known as 'Sangkan Paraning Dumadi dance' or the dance that expresses the origin of human life on earth. The researchers seek to uncover the cultural and philosophical meaning of the dance. This research uses a descriptive qualitative approach, and the data collection procedure was carried out by interview, observation, and documentation techniques. The results show that Sodoran dance has deep philosophical and religious values which are rigidly based on ancestral guidelines. The norms and customs are clearly depicted in the attributes and movement of the dance. In addition, the components of Sodoran dance such as body movement, rhythm, outfits, steps, and statues are closely entwined with the culture and philosophy of Tenggerese people.